2016
DOI: 10.1177/0309324716671857
|View full text |Cite
|
Sign up to set email alerts
|

A study on non-linear post-buckling behavior of tapered Timoshenko beam made of functionally graded material under in-plane thermal loadings

Abstract: In the present work, the non-linear post-buckling load-deflection behavior of tapered functionally graded material beam is studied for different in-plane thermal loadings. Two different thermal loadings are considered. The first one is due to the uniform temperature rise and the second one is due to the steady-state heat conduction across the beam thickness leading to non-uniform temperature rise. The governing equations are derived using the principle of minimum total potential energy employing Timoshenko bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The total strain energy ( U ) of the beam is given by, U = U ax + U sh + U th , where U ax , U sh and U th denote the strain energies due to normal strain in the axial direction, due to transverse shear strains and due to thermal pre-stress, 36 respectively. The expressions of U ax , U sh and U th are derived as given below…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The total strain energy ( U ) of the beam is given by, U = U ax + U sh + U th , where U ax , U sh and U th denote the strain energies due to normal strain in the axial direction, due to transverse shear strains and due to thermal pre-stress, 36 respectively. The expressions of U ax , U sh and U th are derived as given below…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The post-buckling equilibrium path for HH beams under both UTR and HC is not furnished in the present work as it is available in the study by Paul and Das. 21
Figure 4.Post-buckling load–deflection path of CC tapered ( n = 0.5) stainless steel/silicon nitride beam with k = 1.0: (a) UTR and (b) HC.
…”
Section: Resultsmentioning
confidence: 99%
“…The literature review reveals that studies on tapered FGM beams under thermal loading are scarce. To the best knowledge of the authors, the research findings in this regard are available in the studies by Niknam et al 20 and Paul and Das 21 . In the study by Niknam et al, 20 static analysis under UTR based on EBT is reported presenting limited results for deformed configuration of fixed-ended beam.…”
Section: Introductionmentioning
confidence: 99%
“…For detailed static and dynamic investigations of structural members made of FGMs, one may see the literature. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Various special methods such as chemical and physical deposition, powder stacking, plasma spraying, and sintering have been used to fabricate FGMs. It is recently reported that in production of FGMs, internal porosities may appear inside the material structure due to the huge difference between the solidification temperatures of the material constituents during the sintering process.…”
Section: Introductionmentioning
confidence: 99%